Observation of an excited B±c meson state with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Colombo, Tommaso; Davygora, Yuriy; Dietzsch, Thorsten; Dunford, Monica; Giulini, Maddalena; Hanke, Paul; Djuvsland, Julia Isabell; et al. (Physical review letters, 2014)
A search for excited states of the B±c meson is performed using 4.9 fb−1 of 7 TeV and 19.2 fb−1 of 8 TeV pp collision data collected by the ATLAS experiment at the LHC. A new state is observed through its hadronic transition to the ground state, with the latter detected in the decay B±c→J/ψπ±. The state appears in the m(B±cπ+π−)−m(B±c)−2m(π±) mass difference distribution with a significance of 5.2 standard deviations. The mass of the observed state is 6842±4±5 MeV, where the first error is statistical and the second is systematic. The mass and decay of this state are consistent with expectations for the second S-wave state of the B±c meson, B±c(2S).